EXPLORING THE SOCIAL LEGACY OF PARALYMPIC GAMES FOR DISABLED PEOPLE - Kirakosyan, Lyusyena; Seabra Junior, Manoel Osmar [UNESP] (Inst Fed Education, Science & Technology Of Goias, Campus Inhumas, 2018)
While the concept of legacy of sporting mega-events has been highly debated and filled with the promise to deliver tangible and measurable benefits, in the context of the Paralympics, defining legacy has been a challenge, due to a lack of universally understood and accepted nature and objectives of the Paralympic Games themselves. Although many authors and disability rights activists expect the Paralympics to accelerate agenda of inclusion of disabled people, a growing number of studies found that the Paralympics misrepresent disability and the reality of disabled people, and consequently reinforce negative stereotypes. Informed by critical disability studies, the central research aim of this article is to examine the social legacies of the 2012 and 2016 Paralympic Games for disabled people as identified in the media coverage of three selected periodicals, The Guardian, and O Globo. The article presents a summary of the qualitative analysis of the media coverage related to the topic of Paralympic legacy and disability rights, highlights its central themes and offers a discussion of the findings through the lens of critical disability studies.
Keywords: Paralympics; legacy; disability rights; critical disability theory; social inclusion